2001
DOI: 10.1200/jco.2001.19.8.2123
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Quality of Life Before and After Radical Radiotherapy in Non–Small-Cell Lung Cancer

Abstract: This study is the first to describe palliation and changes in QoL in radically irradiated patients with NSCLC. Radical radiotherapy offers palliation of respiratory symptoms and improved QoL in a substantial proportion of patients with NSCLC who have relatively good prognostic features. Although tumor reduction is associated with palliation of respiratory symptoms, it cannot serve as a surrogate for palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
2
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 26 publications
2
50
2
8
Order By: Relevance
“…The dependent variable in these regression analyses was overall QoL (EORTC QLQ-30, item 30); age, gender and histology (SCLC/NSCLC), were included as potential confounders. Since fatigue is the most frequently reported cancer-related side-effect, being of significant influence on QoL, we also adjusted for this variable [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable in these regression analyses was overall QoL (EORTC QLQ-30, item 30); age, gender and histology (SCLC/NSCLC), were included as potential confounders. Since fatigue is the most frequently reported cancer-related side-effect, being of significant influence on QoL, we also adjusted for this variable [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…More apparent predictors for QoL found in this study appeared to be gender, tumor stage, and fatigue. The latter finding is not surprising, as fatigue is identified as the most predominant factor that influences overall QoL [18,19,21]. In addition, the more persistent worsening of some symptoms and functioning scores may be caused by the occurrence of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on quality of life was measured with the EORTC quality of life questionnaire QLQ-C30 (Wymenga et al 1999, Langendijk et al 2001. Questions were added to evaluate the specific carcinoid symptoms, such as flushes and abdominal cramps, and the specific sideeffects of IFN such as chills and muscle pain.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] However, progress has been incremental over several decades, and nevertheless the great majority of people with metastatic or recurrent cancer will die from their disease. 4,5 Although a significant number of advanced cancer patients respond to first-line regimens, survival rates continue to remain fairly low, with the main outcome being largely palliative. 2,6,7 Nevertheless, it is becoming apparent that treatment may improve quality of life even if it does not lengthen it.…”
mentioning
confidence: 99%
“…12 In contrast to these studies, no significant group differences were found in patientreported outcome scores between tumor responders and nonresponders (with the exception of chest pain) in a study involving patients with nonsmall cell lung carcinoma (n ϭ 130) after radical radiotherapy. 4 Moreover, the authors reported that a substantial number of nonresponding patients attained symptom palliation and improved health-related quality of life. Finally, in a study examining the relation between patient well-being and disease response among 155 breast carcinoma patients, 61% of responders and 17% of those with PD reported improved well being, whereas 24% of partial responders reported diminished well being.…”
mentioning
confidence: 99%